Withania somnifera (L.) Dunal: Opportunity for Clinical Repurposing in COVID-19 Management - Saggam, Akash; Limgaokar, Kirti; Borse, Swapnil; Chavan-Gautam, Preeti; Dixit, Santosh; Tillu, Girish; Patwardhan, Bhushan (Frontiers in Pharmacology, 2021)
As the COVID-19 pandemic is progressing, the therapeutic gaps in conventional management have highlighted the need for the integration of traditional knowledge systems with modern medicine. Ayurvedic medicines, especially Ashwagandha (Withania somnifera (L.) Dunal, WS), may be beneficial in the management of COVID-19. WS is a widely prescribed Ayurvedic botanical known as an immunomodulatory, antiviral, anti-inflammatory, and adaptogenic agent. The chemical profile and pharmacological activities of WS have been extensively reported. Several clinical studies have reported its safety for use in humans. This review presents a research synthesis of in silico, in vitro, in vivo, and clinical studies on Withania somnifera (L.) Dunal (WS) and discusses its potential for prophylaxis and management of COVID-19. We have collated the data from studies on WS that focused on viral infections (HIV, HSV, H1N1 influenza, etc.) and noncommunicable diseases (hypertension, diabetes, cancer, etc.). The experimental literature indicates that WS has the potential for 1) maintaining immune homeostasis, 2) regulating inflammation, 3) suppressing pro-inflammatory cytokines, 4) organ protection (nervous system, heart, lung, liver, and kidney), and 5) anti-stress, antihypertensive, and antidiabetic activities. Using these trends, the review presents a triangulation of Ayurveda wisdom, pharmacological properties, and COVID-19 pathophysiology ranging from viral entry to end-stage acute respiratory distress syndrome (ARDS). The review proposes WS as a potential therapeutic adjuvant for various stages of COVID-19 management. WS may also have beneficial effects on comorbidities associated with the COVID-19. However, systematic studies are needed to realize the potential of WS for improving clinical outcome of patients with COVID-19.